Regulation of mycobacterial infection by macrophage Gch1 and tetrahydrobiopterin - Eileen McNeill (Nature Portfolio, 2018)
Inducible nitric oxide (NO) synthase (iNOS) is essential in the response to mycobacterial infection, yet NOS signalling can occur through NO-dependent or NO-independent pathways. Here the authors show macrophage Gch1 and tetrahydrobiopterin mediate NO-independent control of Mycobacterial infection.